2017
DOI: 10.1227/neu.0000000000001240
|View full text |Cite
|
Sign up to set email alerts
|

Different Risk Factors of Proximal Junctional Kyphosis and Proximal Junctional Failure Following Long Instrumented Fusion to the Sacrum for Adult Spinal Deformity: Survivorship Analysis of 160 Patients

Abstract: PJK developed at a median of 17 months and PJF at a median of 3 months. A high body mass index was an independent risk factor for PJK, whereas older age, osteoporosis, uppermost instrumented vertebra level at the thoracolumbar junction, and greater preoperative sagittal vertical axis were risk factors for PJF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
105
1
1

Year Published

2018
2018
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(114 citation statements)
references
References 29 publications
7
105
1
1
Order By: Relevance
“…While our results probably underestimated the true 2-year PJK rate, it is also well documented that the majority of PJK happens within the first few months following the surgical procedure. 13,28,37…”
Section: Discussionmentioning
confidence: 99%
“…While our results probably underestimated the true 2-year PJK rate, it is also well documented that the majority of PJK happens within the first few months following the surgical procedure. 13,28,37…”
Section: Discussionmentioning
confidence: 99%
“…In yet another study, Ghiselli et al 24 found that patients who underwent a 1-level fusion were more likely to develop clinical ASD than those who underwent a multilevel fusion. 52 Similarly, Hilibrand et al 29 found more incidences of ASD after 1-level cervical fusions than after multilevel arthrodesis. Given the aforementioned controversies, further study is required.…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies found increased rates of ASD, specifically PJK, in patients who underwent surgical correction and had a higher preoperative SVA. 52 In our subset analysis, the majority of patients had a normal preoperative SVA (as measured on standing 36-inch plain scoliosis radiographs) ( Table 1). Although a limitation in our study is that upright scoliosis radiographs to use for the determination of perioperative SVA were not available for all patients, normal preoperative SVA parameters and mild SVA changes might have contributed to our low rate of ASD and reoperation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most instances of PJK occur within 3 months of surgery. 2,4,5 There are surgical, radiographic, and patient-specific risk factors that may lead to the development of PJK. 2,3,[6][7][8][9][10] Fracture at the upper instrumented vertebrae is the most common mechanism for the development of PJK.…”
Section: Introductionmentioning
confidence: 99%